(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
The Macadamia nut belongs to the Proteacea family and is native to Southeast Queensland in Australia. In Venezuela, it has been cultivated for more than 25 years. Macadamia flowers are perfect, they occur in clusters on the branches of at least two years, which contain more than 200 flowers, although only a small percentage turns into nuts ripe; that is, 20 ripe fruits per cluster can be successfully expected. This research aims to study the development stages of flowering and fruiting in two species of macadamia, in the town of Cubiro, Lara state. Twenty 14-year-old plants were selected to establish the sequence of morphological changes and events that occur in inflorescence development. 20 inflorescences were marked in initial state per plant and then the variables were evaluated: length and number of flowers of the inflorescence. In fruits, the variables were recorded: diameter from day 42 to physiological maturity and number of fruits / bunch. The evaluations were carried out weekly. From the moment the flower bud begins to develop, 40 days elapse and that is when the flower buds become apparent. At the end of the inflorescence growth, thickened flowers were observed, pale green in color, indicating the proximity of the opening. At 50 days, the floral anthesis begins acropetably and lasts up to 57 days. The period from flower bud formation to anthesis developed in approximately 60 days.